Transparent metal oxide films based sensors for solar tracking applications - Yakuphanoğlu, Fahrettin (Elsevier Sci Ltd, 2016)
Titanium dioxide:zinc oxide (TiO2:ZnO) composite thin films were prepared onto glass and p-type silicon substrates by the sol-gel spin coating technique. The composite metal oxide films indicate a high transmittance more than 90% in visible region. Optical constants such as optical band gap and refractive index of the films were determined using transmittance and reflectance spectra. TiO2:ZnO/p-Si diodes exhibited a high photocurrent responsivity under various solar illuminations. Electronic parameters like ideality factor, series resistance and barrier height were determined from I-V characteristic curves, Cheung model and Norde equations. The capacitance-voltage and conductance-voltage of the diodes were measured in the range from 10 kHz to 1 MHz. The capacitance of the diodes exhibited a decrease in capacitance and increase in conductance with increasing frequency. The obtained results suggest that TiO2:ZnO/p-Si diodes can be used as a sensor in optic communications and optoelectronic applications. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Nano-structures; Electrical properties; Electron microscopy